The Common European Asylum System: reality, wishful legal thinking or synonym for shifting responsibility for failures of national asylum systems to the European level? - Hailbronner, Kay (2014)
Asylum in the European Union is granted to people in need of international protection. Art. 18 of the EU Charter of fundamental Rights and Freedoms guarantees the right to asylum with due respect for the rules of the Geneva Convention of 1951 and in accordance with the treaty establishing the European Union.